Pengaruh Good Corporate Governance, Leverage dan Firm Size terhadap Kinerja Keuangan Pada Perusahaan Sektor Mining yang Tercatat Di Bursa Efek Indonesia Tahun 2019 – 2022 - Pitaloka, Puspa Ayu; Hartono, Ulil (Jurnal Ilmu Manajemen, 2024)
This research aims to determine the effect of good corporate governance, leverage, and firm size on the financial performance of companies as measured by return on assets (ROA). The good corporate governance variable is proxied by board size, board independence and audit committee, while leverage is proxied by the debt-to-equity ratio (DER). The objects of the study are mining sector companies listed on the Indonesia Stock Exchange for the period 2019-2022. The sampling technique used is purposive sampling, resulting in 41 companies that meet the criteria and mining sector companies that publish annual reports for 2019-2022. This study employs multiple linear regression techniques using IBM SPSS Statistics software. The results show that board size, leverage and firm size have a negative effect on the financial performance, while board Independence and audit committee have no effect on the financial performance.  The implications that can be applied by mining sector companies are reducing the size of the board of directors, optimising funding sources other than debt and reducing the number of high-maintenance assets to improve their financial performance.